2021
DOI: 10.2298/tsci190324293i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variable thermal conductivity on the MHD boundary-layer of Casson-nanofluid over a moving plate with variable thickness

Abstract: The effect of variable thermal conductivity on the characteristics of heat transfer and mechanical properties of a moving surface on a casson-nanofluid flow as a coolant has been studied in this paper. We used similarity transformation method to transform the equations of the governing boundary layer into ordinary differential equations which are solved numerically using a mix of fourth order Runge Kutta method and find root technique. Different values relevant parameters have been studied on the features of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Sridhar and Lakshmi (2020) discussed nanofluid flow on elongating sheet through the double stratified medium using implicit finite difference method concludes that velocity slip parameter reduces concentration profile. Finally, Ismail et al (2021) analyzed Casson nanofluid flow with variable thermal conductivity, and variable thickness of the fluids concluded that using Casson nanofluid will increase the movement of heat value over the exterior, which will accelerate the cooling process, and this, in turn, leads to improve the heat treatment process. Also, Casson nanofluid increases the shear stress above the surface and the level of mass relocation over the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Sridhar and Lakshmi (2020) discussed nanofluid flow on elongating sheet through the double stratified medium using implicit finite difference method concludes that velocity slip parameter reduces concentration profile. Finally, Ismail et al (2021) analyzed Casson nanofluid flow with variable thermal conductivity, and variable thickness of the fluids concluded that using Casson nanofluid will increase the movement of heat value over the exterior, which will accelerate the cooling process, and this, in turn, leads to improve the heat treatment process. Also, Casson nanofluid increases the shear stress above the surface and the level of mass relocation over the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Unsteady parameter A = 0.1, 0.3, 0.5, 0.7, 1, 2, 3 as in [34] 12. Thermal conductivity parameter b = 1, 1.5, 2, 3 as in [53] Table 4. The values of thermo-physical properties of magnetic particles and base fluid are as follows [46,54,55].…”
mentioning
confidence: 99%